Human psychology in extreme conditions occupation of the Pskov region during the Great Patriotic War (International Journal of Scientific Research and Management (IJSRM), 2021)
The article is aimed at understanding human psychology during the Nazi occupation at the regional level in the context of personal history. The psychology of a civilian in extreme military conditions has not been sufficiently researched, and the reason lies in an interdisciplinary approach. All researchers of military psychology emphasize that the psychology of a person who is in extreme conditions, which are military actions, significantly differs from the psychology of a person in peaceful conditions in specific features, states and qualities. In extreme conditions, both the lowest and the highest qualities of the human spirit are clearly manifested in a person. The entire military psychology of a person is formed during a war and persists for a long time after hostilities. The article presents four personal stories of the inhabitants of the occupied Pskov territory during the Great Patriotic War, which state the presence of constant anxiety, fear and despair. The article discusses the main conditions of a person in extreme conditions, the stages of their development. In all extreme situations, a person’s moral conditioning and mental state play a decisive role; they determine the readiness for deliberate, confident and prudent actions in critical moments. It is concluded that the use of field research to collect the oral personal history of civilians can significantly enrich knowledge about human psychology in the extreme conditions of the Great Patriotic War.